If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x = 7x + 8 Reorder the terms: 9x = 8 + 7x Solving 9x = 8 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. 9x + -7x = 8 + 7x + -7x Combine like terms: 9x + -7x = 2x 2x = 8 + 7x + -7x Combine like terms: 7x + -7x = 0 2x = 8 + 0 2x = 8 Divide each side by '2'. x = 4 Simplifying x = 4
| -5-3(m-4)=19 | | 2y*5y= | | 9+5x=64 | | (8t-2)=3(t+1)+6 | | 50-15= | | -60=-3(3n+5) | | 5(y+4)=6(Y-2) | | 6-6x=-18 | | 11k+9k= | | 6x-7x^5=22x-339 | | 6(x-2)=-42 | | 7.8x-1.5=14.1 | | 24=4(1-x) | | 12x-11=25 | | -6(x+1)-10=24+8 | | -16=4(k+1) | | x--12=-7 | | 6(4z-1)-5(z+7)=6(z+1) | | 8x+16-7x=-6-11 | | 8x+16-7x=-1-11 | | 5.7(x-1)=-0.3x+36.3 | | 4x-12=(3x+4)3 | | 4t-6=-10 | | 8(y-3)=3y-54 | | -4y-11=5y+25 | | h^2-9h+20=0 | | -2y-12=6y+36 | | 8y-2=6y+2 | | -2y-9=6y+45 | | ln(2x+3)-ln(4-x)=0 | | 15+8x-7=3(5x+6) | | 3(5c-1)-2=13c+9 |